Cold deformation method for improving corrosion resistance and conductivity of bipolar plate of fuel cell

By performing quasi-static uniaxial stretching of austenitic stainless steel and introducing high-density dislocations, the problem of insufficient corrosion resistance and conductivity of stainless steel bipolar plates in fuel cell environments is solved, and significant corrosion resistance and conductivity are improved.

CN119859739APending Publication Date: 2025-04-22NORTHEASTERN UNIV CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510216297.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing stainless steel bipolar plates have insufficient corrosion resistance and conductivity in fuel cell environments, resulting in accelerated corrosion and reduced performance.

Method used

By performing quasi-static uniaxial stretching of austenitic stainless steel, high-density dislocation is introduced, and the nucleation sites of the passivation film and the diffusion of Cr elements are increased, thereby improving corrosion resistance and electrical conductivity.

Benefits of technology

It significantly improves the corrosion resistance and conductivity of stainless steel in PEMFC environment, increases self-corrosion potential, decreases self-corrosion current density, and improves conductivity, which is better than the 2025 index requirements of the US Department of Energy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859739A_ABST
    Figure CN119859739A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of stainless steel, and discloses a cold deformation method for improving corrosion resistance and conductivity of a bipolar plate of a fuel cell. The nitrogenous austenitic stainless steel is subjected to quasi-static uniaxial stretching, and the stretching direction is the longitudinal direction or the transverse direction of the plate; the nitrogen-containing austenitic stainless steel comprises the following components: 0.02% of C; 19%-26% of Cr; 5%-15% of Ni; 0.1% to 0.5% of N; fe: the balance. And the tensile deformation is 10%-30%, so that the dislocation density in a deformed structure is increased by 114.71%-394.11%, and the corrosion resistance and conductivity of the nitrogen-containing austenitic stainless steel in a PEMFC cathode working environment are improved. The stainless steel is subjected to proper plastic deformation, a proper amount of dislocation is introduced into a microscopic structure, and the corrosion resistance and the conductivity of the stainless steel bipolar plate are remarkably improved by promoting the formation of a passive film and increasing the binding force of the passive film and a matrix.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of stainless steel, and in particular to a cold deformation method for improving the corrosion resistance and electrical conductivity of a fuel cell bipolar plate. Background Art

[0002] Stainless steel is widely used in energy, electricity, chemical industry and other fields due to its excellent mechanical and corrosion resistance, as well as the manufacturing material of bipolar plates for proton exchange membrane fuel cells. The corrosion resistance mechanism of stainless steel is that the elements such as Cr on its surface and the oxygen in the air form a very thin, dense and adhesive passivation film, which acts as a protective barrier to isolate the corrosive medium from the substrate. The deformation amount at different positions during the microchannel stamping process of stainless steel bipolar plates is different, which will lead to differences in local microstructures and affect the corrosion resistance. The effect of deformation on corrosion resistance is relatively complex. For austenitic stainless steel, severe deformation may cause part of the austenite to transform into martensite, forming a local corrosion galvanic cell that accelerates corrosion and reduces the corrosion resistance of the bipolar plate. The appropriate amount of dislocation can provide more nucleation sites for the passivation film, resulting in the number of nucleation sites of the passivation film increasing with the degree of deformation, while enhancing the adhesion between the passivation film and the substrate. In addition, dislocations promote the migration of alloying elements such as Cr, thereby accelerating the formation of passivation films. Therefore, it is of great practical significance to improve the corrosion resistance and conductivity of bipolar plates by controlling the deformation of stainless steel.

[0003] Currently, the main material of stainless steel bipolar plates is austenitic stainless steel. Due to its low Cr content, austenitic stainless steel has insufficient corrosion resistance in the PEMFC environment. The present invention introduces high-density dislocations into the structure by tensile deformation of austenitic stainless steel, thereby significantly improving the corrosion resistance and conductivity of stainless steel in the PEMFC environment, thereby improving the long-term service safety of PEMFC. Summary of the invention

[0004] The technical problem to be solved by the present invention is to solve the problem that the corrosion resistance and conductivity of stainless steel in the current fuel cell corrosion environment are insufficient. By tensile deformation of austenitic stainless steel, high-density dislocations are introduced into the structure, the corrosion resistance and conductivity of stainless steel in the PEMFC environment are significantly improved, the self-corrosion potential of stainless steel is increased, and the self-corrosion current density is reduced. The corrosion current density of stainless steel in the simulated fuel cell cathode environment is less than 1μA·cm 2 The contact resistance after 5h of polarization at the cathode working potential is less than 1Ω / cm 2 , conductivity and corrosion resistance are better than the US Department of Energy's 2025 index requirements.

[0005] The technical solution of the present invention is as follows: a cold deformation method for improving the corrosion resistance and conductivity of a fuel cell bipolar plate, wherein nitrogen-containing austenitic stainless steel is subjected to quasi-static uniaxial stretching, and the stretching direction is the longitudinal direction of the plate or the transverse direction of the plate; the nitrogen-containing austenitic stainless steel has the following components: C: 0.02%; Cr: 19%-26%; Ni: 5%-15%; N: 0.1%-0.5%; Fe: balance.

[0006] The stretching deformation amount is 10%-30%, which increases the dislocation density in the deformed structure by 114.71%-394.11%, thereby improving the corrosion resistance and conductivity of nitrogen-containing austenitic stainless steel in the PEMFC cathode working environment.

[0007] After stretching, the self-corrosion potential of nitrogen-containing austenitic stainless steel increased by 1.72%-8.62%, the self-corrosion current density decreased by 27.00%-42.22%, and the corrosion current density decreased by 64.84%-96.88% after 5h of constant potential polarization at the cathode working potential. In addition, the conductivity increased by 24.18%-56.85% after 5h of constant potential polarization at the cathode working potential.

[0008] Preferably, the stretching deformation is 30%, which increases the dislocation density in the deformed structure by 147.06%, thereby improving the corrosion resistance and conductivity of the nitrogen-containing austenitic stainless steel in the PEMFC cathode working environment.

[0009] The self-corrosion potential of nitrogen-containing austenitic stainless steel with a tensile deformation of 30% increased by 8.62%, the self-corrosion current density decreased by 42.22%, the cathode working potential constant potential polarization corrosion current density decreased by 96.88%, and the conductivity under a pressure of 1.4MPa increased by 56.85%.

[0010] A cold deformation method for improving the corrosion resistance and electrical conductivity of a fuel cell bipolar plate comprises the following steps:

[0011] Step 1: subjecting the adopted nitrogen-containing austenitic stainless steel hot-rolled plate to solid solution treatment, keeping the temperature at 950-1200°C for 5-120 minutes, and then cooling the plate to room temperature with water, so that the surface becomes smooth;

[0012] Step 2: The nitrogen-containing austenitic stainless steel described in step 1 is subjected to a tensile deformation of 10-30% along the longitudinal or transverse direction of the plate.

[0013] By subjecting austenitic stainless steel to quasi-static uniaxial stretching, an appropriate amount of dislocations are introduced into the deformed structure, providing a large number of nucleation sites during the formation of the stainless steel passivation film. A large number of dislocations promote the diffusion of Cr and N elements into the passivation film. The synergistic effect of the two significantly improves the corrosion resistance and conductivity of stainless steel in the PEMFC cathode working environment.

[0014] Compared with the prior art, the present invention has the following beneficial effects: the corrosion resistance and electrical conductivity of stainless steel bipolar plates in the working environment of fuel cells are relatively poor. Improving the corrosion resistance by increasing alloying elements will bring cost issues. The present invention introduces an appropriate amount of dislocations into the microstructure by performing appropriate plastic deformation on stainless steel, and significantly improves the corrosion resistance and electrical conductivity of stainless steel bipolar plates by promoting the formation of passivation film and increasing the bonding force between the passivation film and the matrix. Compared with the prior art, the present invention is more mature in the process of stretching as plastic deformation, has a lower production cost, a relatively simple process, and little restriction on materials and equipment. It can effectively improve the corrosion resistance and electrical conductivity of stainless steel bipolar plates, increase service life and reduce costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1-Figure 4 The microstructures of Example 1 with different tensile deformations are shown in Figure 1; (a1) is the inverse pole figure of Example 1 at 0% deformation; (a2) is the dislocation distribution diagram of Example 1 at 0% deformation; (a3) ​​is the average dislocation density of Example 1 at 0% deformation; (b1) is the inverse pole figure of Example 1 at 10% deformation; (b2) is the dislocation distribution diagram of Example 1 at 10% deformation; (b3) is the average dislocation density of Example 1 at 10% deformation; (c1) is the inverse pole figure of Example 1 at 30% deformation; (c2) is the dislocation distribution diagram of Example 1 at 30% deformation; (c3) is the average dislocation density of Example 1 at 30% deformation; (d1) is the inverse pole figure of Example 1 at 50% deformation; (d2) is the dislocation distribution diagram of Example 1 at 50% deformation; (d3) is the average dislocation density of Example 1 at 50% deformation.

[0016] Figure 5-Figure 6 The grain size distribution diagrams of different tensile deformations are shown in Figure 1. (a4) is the average grain size of Example 1 at 0% deformation; (b4) is the average grain size of Example 1 at 0% deformation; (c4) is the average grain size of Example 1 at 30% deformation; (d4) is the average grain size of Example 1 at 50% deformation.

[0017] Figure 7-Figure 8 Schematic diagram of microscopic angle distribution of different tensile deformations. (a5) is the size angle and special grain boundary ratio of Example 1 at 0% deformation; (b5) is the size angle and special grain boundary ratio of Example 1 at 10% deformation; (c5) is the size angle and special grain boundary ratio of Example 1 at 30% deformation; (d5) is the size angle and special grain boundary ratio of Example 1 at 50% deformation.

[0018] Fig. 9 Example 1 at 70°C, 0.0005 MH 2 SO 4+2ppmF - Potentiodynamic polarization curves in a solution simulating a fuel cell cathode (with air);

[0019] Fig.10 Example 1 at 70°C, 0.0005 MH 2 SO 4 +2ppmF - Potentiodynamic polarization curves in a solution simulating a fuel cell cathode (with air);

[0020] Fig.11 Example 1 at 70°C, 0.0005 MH 2 SO 4 +2ppmF - Simulated fuel cell cathode in solution (0.23V VS. Impedance spectrum curves under MSE (with air) environment. DETAILED DESCRIPTION

[0021] The various plastic deformation modes of the present invention are not limited by the following examples, and any improvements and changes within the scope of protection required by the claims of the present invention are within the protection scope of the present invention. The following describes the implementation mode of the present invention in detail in combination with the examples and drawings, and further verifies the beneficial effects of the present invention.

[0022] The object of the present invention is to provide a cold deformation method for improving the corrosion resistance and electrical conductivity of a fuel cell bipolar plate.

[0023] A cold deformation method for improving the corrosion resistance and conductivity of a fuel cell bipolar plate comprises the following steps:

[0024] Step 1: The nitrogen-containing austenitic stainless steel hot-rolled plate is solution treated, kept at 1050°C for 20 minutes, then water-cooled to room temperature, and the surface is polished to be smooth.

[0025] Step 2: The nitrogen-containing austenitic stainless steel plate described in step 1 is stretched and deformed, and the plastic deformation is stopped immediately when the deformation reaches 0%, 10%, 30% and 50% respectively.

[0026] The nitrogen-containing austenitic stainless steel comprises the following components: C: 0.02%; Cr: 19%-26%; Ni: 5%-15%; N: 0.1%-0.5%; and Fe: the remainder.

[0027] The low-cost, high-corrosion-resistant stainless steel for fuel cell bipolar plates that has undergone the above plastic deformation treatment is subjected to electrochemical testing simulating fuel cell operating conditions, containing 2ppmF - 0.0005 mol / L H 2 SO 4The aqueous solution was heated to 70°C in a water bath, and air was continuously introduced into the electrolyte at a flow rate of 20 ml / min. First, the working electrode was potential polarized at -1.37 V vs. MSE for 5 min to remove the native oxide film formed in the atmosphere. All electrochemical measurements were performed when the open circuit potential OCP reached a steady-state value. Potentiodynamic polarization scans were performed at a scan rate of 1 mV / s. Constant potential polarization was performed in an oxygen environment close to 0.23 V vs. MSE, and the change of corrosion current with polarization time was measured. The polarization time was 6 h. The Tafel line extrapolation method was used to obtain the self-corrosion current and self-corrosion potential as a basis for comparing the corrosion resistance of the alloy.

[0028] Example 1: The nitrogen-containing austenitic stainless steel used in the present invention has the following composition: C = 0.02%, Cr = 22%, Ni = 10.5%, N = 0.2%, and the balance is Fe; after being processed into a plate, a quasi-static uniaxial stretching is performed using a tensile testing machine, and the deformation rate is 10 -3 s, when the plastic strain reaches 0%, 10%, 30% and 50% respectively, stop the plastic deformation immediately. Use electric spark wire cutting to sample the uniform deformation area. The samples with different deformation amounts are processed into 10mm×10mm×2mm specimens. The test surface is 10mm×10mm. The back is polished and connected with copper wire. After ensuring the conduction, it is encapsulated with denture base resin and exposed to the test surface. It is polished with 240, 400, 600, 800, 1000, 1200, 1500# sandpaper in turn, washed with deionized water and alcohol and then dried. The electrolyte is 2ppmF - 0.0005 mol / L H 2 SO 4 The aqueous solution was heated to 70°C in a water bath, and air or hydrogen was continuously introduced during the experiment at a flow rate of 20 ml / min. The electrochemical test was performed using a CS2350M electrochemical workstation, using a three-electrode system with stainless steel as the working electrode, a Pt sheet as the counter electrode, and a saturated mercurous sulfate electrode (MSE) as the reference electrode. All experiments were measured three times.

[0029] Embodiment 2: The composition of nitrogen-containing austenitic stainless steel is as follows: C=0.02%, Cr=19%, Ni=15%, N=0.1%, and the balance is Fe; the tensile deformation is the same as that of Embodiment 1.

[0030] Embodiment 3: The composition of nitrogen-containing austenitic stainless steel is as follows: C=0.02%, Cr=26%, Ni=5%, N=0.5%, and the balance is Fe; the tensile deformation is the same as that of Embodiment 1.

[0031] In Examples 1 to 3, the performance is best when the tensile deformation is 30%.

[0032] Comparative Example 1: The composition of the austenitic stainless steel used in the present invention is as follows: C = 0.02%, Cr = 19%, Ni = 11%, Mo = 2.5%, and the balance is Fe; after being processed into a plate, a quasi-static uniaxial stretching is performed using a tensile testing machine, and the deformation rate is 10 -3 s, when the plastic strain reaches 0%, 10%, 30% and 50% respectively, stop the plastic deformation immediately. Use electric spark wire cutting to sample the uniform deformation area. The samples with different deformation amounts are processed into 10mm×10mm×2mm specimens. The test surface is 10mm×10mm. The back is polished and connected with copper wire. After ensuring the conduction, it is encapsulated with denture base resin and exposed to the test surface. It is polished with 240, 400, 600, 800, 1000, 1200, 1500# sandpaper in turn, washed with deionized water and alcohol and then dried. The electrolyte is 2ppmF - 0.0005 mol / L H 2 SO 4 The aqueous solution was heated to 70°C in a water bath, and air was continuously introduced during the experiment at a flow rate of 20 ml / min. The electrochemical test was performed using a CS2350M electrochemical workstation, using a three-electrode system with stainless steel as the working electrode, a Pt sheet as the counter electrode, and a saturated mercurous sulfate electrode (MSE) as the reference electrode. All experiments were measured three times.

[0033] Comparative Example 2: The composition of austenitic stainless steel used in the present invention is as follows: C = 0.02%, Cr = 22%, Ni = 10.5%, N = 0.2%, and the balance is Fe; after being processed into a plate, it is subjected to cold rolling deformation and the cold rolling is stopped immediately when the deformation reaches 0%, 10%, 30% and 50% respectively. The uniform deformation area is sampled by electric spark wire cutting. The samples with different deformation amounts are processed into 10mm×10mm×2mm test specimens, and the test surface is 10mm×10mm. The back is polished and connected with copper wires. After ensuring conduction, it is encapsulated with denture base resin and the test surface is exposed. It is polished with 240, 400, 600, 800, 1000, 1200, 1500# sandpaper in turn, and then washed with deionized water and alcohol and dried. The electrolyte is a 2ppmF - 0.0005 mol / L H 2 SO 4 The aqueous solution was heated to 70°C in a water bath, and air was continuously introduced during the experiment at a flow rate of 20 ml / min. The electrochemical test was performed using a CS2350M electrochemical workstation, using a three-electrode system with stainless steel as the working electrode, a Pt sheet as the counter electrode, and a saturated mercurous sulfate electrode (MSE) as the reference electrode. All experiments were measured three times.

[0034] By polarization curve ( Fig. 9) Tafel extrapolation was performed to obtain the self-corrosion current density I of the example steel. corr and self-corrosion potential E corr , the self-corrosion potential represents the thermodynamic behavior of metal in a corrosive environment, that is, the ease of corrosion, while the self-corrosion current density represents the kinetic behavior of metal in a corrosive environment, that is, the speed of corrosion after corrosion occurs. As shown in Table 1, there is a direct relationship between the corrosion resistance and plastic deformation of stainless steel in the fuel cell cathode (air-permeable) operating environment. As the deformation increases from 0% to 50%, the self-corrosion potential of Example 1, Comparative Example 1, and Comparative Example 2 first increases and then decreases, while the self-corrosion current density first decreases and then increases, and they all have the highest self-corrosion potential and the lowest self-corrosion current density when the deformation is 30%, which indicates their lower corrosion sensitivity and corrosion reaction rate. However, the self-corrosion potentials of Example 1, Comparative Example 1, and Comparative Example 2 with a deformation of 30% were increased by 8.62%, 4.23%, and 6.25%, respectively, compared with a deformation of 0%, and the self-corrosion current density was reduced by 42.22%, 8.68%, and 13.16%, respectively, which shows that tensile deformation has a significant effect on improving the corrosion resistance of Example 1, while the effect is poor for Comparative Example 1. In addition, the effect of cold rolling deformation on improving the corrosion resistance of Comparative Example 2 is lower than that of tensile deformation.

[0035] Table 1 Tafel fitting electrochemical corrosion parameters

[0036]

[0037]

[0038] Constant potential polarization at the cathode working potential can reflect the corrosion resistance of stainless steel under long-term operation of PEMFC. Fig.10 It can be seen that during the constant potential polarization process, the corrosion current density of Example 1 with a deformation of 30% decreased the fastest, and the corrosion current densities of the four deformation amounts were 1.28 μA·cm - 2. 0.07μA·cm - 2. 0.04μA·cm - 2. 0.45μA·cm - 2. The results of constant potential polarization show that compared with the deformation of 0%, the corrosion current density of Example 1 with a deformation of 30% is reduced by 96.88%, so it has the best corrosion resistance. Lower corrosion current density indicates better corrosion resistance under the working environment of cathode and anode environment, less dissolution of stainless steel, and less metal ions released by dissolution, which reduces the toxic effect of metal ions on the membrane electrode and proton exchange membrane of fuel cells.

[0039] The contact resistance between the sample and the carbon paper after the cathode working potential polarization can reflect the change of the conductivity of the stainless steel. Table 2 shows the contact resistance test results of Example 1, Comparative Example 1 and Comparative Example 2 under a pressure of 1.4 MPa after the cathode working potential polarization for 5 hours. As shown in Table 2, the conductivity of Example 1, Comparative Example 1 and Comparative Example 2 with a deformation amount of 30% are increased by 56.85%, 27.46% and 40.50% respectively compared with the deformation amount of 0%, which shows that the tensile deformation has a significant effect on improving the conductivity of Example 1, while the effect is poor for Comparative Example 1. In addition, the effect of cold rolling deformation on improving the conductivity of Comparative Example 2 is lower than that of tensile deformation.

[0040] Table 2 Contact resistance test results (Ω / cm) at 1.4 MPa pressure after 5 h of cathode working potential polarization 2 )

[0041]

[0042]

[0043] The corrosion behavior of stainless steel was studied by AC impedance spectroscopy in a cathodic working environment. Fig.11 It can be seen that Example 1 with a deformation amount of 30% has the largest capacitive reactance arc radius, which indicates that the charge transfer resistance of the corrosion reaction on its surface is the largest, and therefore the corrosion rate is the lowest.

[0044] The present invention relates to a method for improving the corrosion resistance and conductivity of a stainless steel bipolar plate for a fuel cell, which can be widely used in the fields of energy, electricity, chemical industry and daily life, and in particular to the field of manufacturing bipolar plates for proton exchange membrane fuel cells.

[0045] Therefore, in summary, the method of improving the corrosion resistance and conductivity of fuel cell bipolar plates of the present invention has a significant effect in the preparation process of high corrosion-resistant stainless steel bipolar plates for fuel cells.

Claims

1. A cold deformation method for improving the corrosion resistance and conductivity of a fuel cell bipolar plate, characterized in that: The nitrogen-containing austenitic stainless steel is subjected to quasi-static uniaxial stretching, and the stretching direction is the longitudinal direction of the plate or the transverse direction of the plate; the nitrogen-containing austenitic stainless steel has the following components: C: 0.02%; Cr: 19%-26%; Ni: 5%-15%; N: 0.1%-0.5%; Fe: balance.

2. The cold deformation method for improving the corrosion resistance and electrical conductivity of a fuel cell bipolar plate according to claim 1, characterized in that: The stretching deformation amount is 10%-30%, which increases the dislocation density in the deformed structure by 114.71%-394.11%, thereby improving the corrosion resistance and conductivity of nitrogen-containing austenitic stainless steel in the PEMFC cathode working environment.

3. The cold deformation method for improving the corrosion resistance and electrical conductivity of a fuel cell bipolar plate according to claim 2, characterized in that: After stretching, the self-corrosion potential of nitrogen-containing austenitic stainless steel increased by 1.72%-8.62%, the self-corrosion current density decreased by 27.00%-42.22%, and the corrosion current density decreased by 64.84%-96.88% after constant potential polarization at the cathode working potential for 5 hours; the conductivity increased by 24.18%-56.85% after constant potential polarization at the cathode working potential for 5 hours.

4. The cold deformation method for improving the corrosion resistance and electrical conductivity of a fuel cell bipolar plate according to claim 2, characterized in that: The stretching deformation amount is 30%, which increases the dislocation density in the deformed structure by 147.06%, thereby improving the corrosion resistance and electrical conductivity of the nitrogen-containing austenitic stainless steel in the PEMFC cathode working environment.

5. The cold deformation method for improving the corrosion resistance and electrical conductivity of a fuel cell bipolar plate according to claim 4, characterized in that: After stretching, the self-corrosion potential of nitrogen-containing austenitic stainless steel increased by 8.62%, the self-corrosion current density decreased by 42.22%, and the constant potential polarization corrosion current density at the cathode working potential decreased by 96.88%; the conductivity under a pressure of 1.4MPa increased by 56.85%.

6. The cold deformation method for improving the corrosion resistance and electrical conductivity of a fuel cell bipolar plate according to any one of claims 1 to 5, characterized in that: The steps include: Step 1: subjecting the adopted nitrogen-containing austenitic stainless steel hot-rolled plate to solid solution treatment, keeping the temperature at 950-1200°C for 5-120 minutes, and then cooling the plate to room temperature with water, so that the surface becomes smooth; Step 2: The nitrogen-containing austenitic stainless steel described in step 1 is subjected to a tensile deformation of 10-30% along the longitudinal or transverse direction of the plate.